(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The aim of this study is to investigate the role of communicative situations in shaping the functioning of speech acts in English discourse. Specifically, the research seeks to identify how different social, cultural, and contextual factors influence the choice, interpretation, and pragmatic realization of speech acts such as requests, apologies, compliments, and refusals. By analyzing authentic conversational data, the study aims to reveal patterns of interaction that demonstrate the interdependence between situational context and speech act performance. Ultimately, the research aspires to contribute to a deeper understanding of the pragmatic mechanisms that govern effective communication, offering insights applicable to language teaching, intercultural communication, and the development of pragmatic competence in learners of English. The study uses a qualitative-pragmatic approach to examine how communicative situations affect the functioning of speech acts in English. It focuses on understanding the role of social and contextual factors in shaping the choice and interpretation of speech acts such as requests, refusals, apologies, and compliments. Spoken corpora: Selected passages from the British National Corpus (BNC) and the London-Lund Corpus of Spoken English.